Upaya Meningkatkan Ketersediaan Hmt Dan Kapasitas Tampung Ternak Melalui Penanaman Hijauan Sistem Tiga Strata - Danang Biyatmoko (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
The study aims to determine the effect of planting system and cutting age on the level of provision of forage fodder is generated ( fresh , dry matter (DM ) ) and carrying capacity. The research method uses completely randomized factorial design 2 x 4 x 2 replications , using a land plot of 250 m2 per experimental unit . The first factor is the cropping system consists of a type of grass ( R1 ) , TSS models are grass + legume ( R2 ) and the second factor is the age of cutting grass consists of 30 days ( P1 ) , 45 ( P2 ) , 50 ( P3 ) , 60 ( P4 ) , The variables observed is an increase in the production of fresh forage and dry matter (DM ) and carrying capacity. Research indicates that three strata System (TSS) with a superior combination of types of forage legume bushes /shrubs and trees were able to improve the level of production of forage fodder is higher by increased production of fresh forage up to 29.28 % ( R2P3 ) and increased production of dry matter ( DM ) up to 41.39 % higher than the control ( R1P1 ) by planting a single type of grass only. Increased productivity of forages with three strata system   ( TSS ) is also able to increase livestock carrying capacity or a stocking rate of 128 AU/ha/year to 165 AU/ha/year